Attitudes Toward Divorce, Commitment, and Divorce Proneness in First Marriages and Remarriages. Issue 2 (14th March 2013) - Whitton, Sarah W.; Stanley, Scott M.; Markman, Howard J.; Johnson, Christine A.
<x xml:space="preserve">Abstract</x> A random multistate sample of married individuals (N = 1, 931) was used to explore whether more positive attitudes toward divorce and weaker commitment to marriage may contribute to the greater instability of remarriages than first marriages. Remarried adults, whether or not they brought children from a previous union into the remarriage, reported marital quality (happiness and conflict) equal to those in first marriages. They also reported more positive attitudes toward divorce, which were associated with higher divorce proneness (i.e., thinking about and taking actions toward divorce). Marriage type interacted with marital quality to predict divorce proneness, such that the association between low marital quality and divorce proneness was stronger for remarried individuals than for those in first marriages. This suggests that remarried adults may be more likely than adults in first marriages to take steps toward divorce when experiencing marital distress, possibly reflecting a weaker commitment to marriage.